Trends in the use of medications with insomnia side effects and the implications for insomnia among US adults. (15th May 2020) - Do, Duy
Abstract: Americans are increasingly consuming pharmaceuticals that although effective in treating their focal indication, include insomnia as a side effect. Regardless, no studies have documented trends in the concurrent use of these medications and their implications for insomnia among community‐dwelling adults. Using a nationally representative sample of US adults from the 1999–2016 National Health and Nutrition Examination Survey (NHANES), this study shows that the concurrent use of medications with insomnia as a potential side effect ("insomnia side effects" hereafter) has increased considerably in the past two decades. Between 1999 and 2016, the use of one and two or more medications with insomnia side effects increased by 66% and 164%, respectively. Compared to non‐users, respondents who took two or more of these medications were more likely to report insomnia symptoms (odds ratio [OR] = 1.78; 95% confidence interval [CI], 1.22 to 2.60), daytime sleepiness symptoms (OR = 1.73; 95% CI, 1.16 to 2.60) and difficulty with at least two daytime activities due to sleepiness or tiredness (OR = 1.96; 95% CI, 1.28 to 3.00). These findings highlight the need for insomnia screenings among patients who consume medications with insomnia side effects. They also emphasize the increased risks of insomnia associated with polypharmacy.